Renal function and long term mortality after unstable angina/non-ST segment elevation myocardial infarction treated very early and predominantly with percutaneous coronary intervention. Issue 8 (14th July 2004) - Mueller, C; Neumann, F-J; Perruchoud, A P; Buettner, H J
Abstract : Objectives: To quantify the impact of baseline renal function on in-hospital and long term mortality in patients with unstable angina/non-ST elevation acute myocardial infarction (UA/NSTEMI) treated with a very early invasive strategy. Design: Prospective cohort study of 1400 consecutive patients with UA/NSTEMI undergoing coronary angiography and subsequent coronary stenting of the culprit lesion as the primary revascularisation strategy within 24 hours of admission. Patients were stratified according to calculated glomerular filtration rate (GFR) on admission. Results: In-hospital mortality was 0% among patients with a GFR ⩾ 130 ml/min/1.73 m 2, 0.4% with a GFR of 90–129 ml/min/1.73 m 2, 2.6% with a GFR of 60–89 ml/min/1.73m 2, and 5.1% with a GFR of < 60 ml/min/1.73 m 2 . Cumulative three year survival rates were 92.6%, 95.5%, 91.9%, and 76.8%, respectively. Patients with a GFR of < 60 ml/min/1.73 m 2 were four times more likely to die in hospital (hazard ratio (HR) 4.0, 95% confidence interval (CI) 1.8 to 9.1; p  =  0.001) and four times more likely to die during long term follow up (HR 4.0, 95% CI 2.5 to 6.4; p < 0.001). After adjusting for potential confounders, a GFR of < 60 ml/min/1.73 m 2 remained a strong independent predictor of long term mortality (HR 2.6, 95% CI 1.5 to 4.5; p  =  0.001). Conclusions: Baseline renal function is a strong independent predictor of in-hospital and long term mortality after UA/NSTEMI treated with very early revascularisation.